2019
DOI: 10.37134/jictie.vol6.1.2019
|View full text |Cite
|
Sign up to set email alerts
|

Gender and Game Genres Differences in Playing Online Games

Abstract: Online games are currently popular among teenagers as a way to entertain their time and having fun. Some claimed that by playing games could enhance learning ability, improved focus and attention, treat depression, less anti-social and many more. However, playing games could also become an addiction where some might involve with physical and health problems. This paper investigated gender-based students’ perceptions on playing games with their daily life. The perceptions study was developed based on ten items … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 10 publications
0
1
0
2
Order By: Relevance
“…The implementation of online learning, for example, integrated video in teaching and learning, has proven to be significant in teaching and learning in various aspects, for example, enhancing student vocabulary [22], [23], knowledge [16], [24]- [28], thinking skills [25], [29], achievements [12], [30]- [32], student engagement [33], communication skills [34], [35], and positive attitudes like satisfaction in learning, motivation and self-confidence [36]- [40]. Nevertheless, previous research has indicated that online learning, such as game-based learning, could support and motivate students in financial literacy through strategies like level progression, rewards and visual designs [41].…”
Section: Promoting Financial Literacy Amongst Students With Online Le...mentioning
confidence: 99%
See 1 more Smart Citation
“…The implementation of online learning, for example, integrated video in teaching and learning, has proven to be significant in teaching and learning in various aspects, for example, enhancing student vocabulary [22], [23], knowledge [16], [24]- [28], thinking skills [25], [29], achievements [12], [30]- [32], student engagement [33], communication skills [34], [35], and positive attitudes like satisfaction in learning, motivation and self-confidence [36]- [40]. Nevertheless, previous research has indicated that online learning, such as game-based learning, could support and motivate students in financial literacy through strategies like level progression, rewards and visual designs [41].…”
Section: Promoting Financial Literacy Amongst Students With Online Le...mentioning
confidence: 99%
“…Subject norm considers the spending behavior of students. The saving habits of parents positively influence the financial literacy of their children [16], and financial literacy always influences perceived behavior control, especially amongst young adults. Financial literacy gives students a sense of perceived behavioral control to execute behavioral intentions in the context of the TPB.…”
Section: Introductionmentioning
confidence: 99%
“…Sebagai contoh, kemahiran serta kreativiti dapat dipertingkatkan menjadi idea yang inovatif melalui digital media (Alwehaibi & Abdulrahman, 2015). Tambahan daripada itu, keterlibatan dalam aspek pendidikan sebagai alat bantu mengajar berasaskan media dan teknologi juga memberi impak yang efektif dalam memotivasikan dan meningkatkan kepekaan remaja semasa belajar di dalam kelas (Hassan et al, 2015).…”
Section: Pengenalanunclassified
“…Tambahan pula, dapatan kajian ini yang telah melaporkan bahawa tidak terdapat perbezaan min penggunaan sumber-sumber sejarah dari aspek pengetahuan, kemahiran dan sikap yang signifikan berdasarkan gender adalah sealiran dengan dapatan kajian Mohd Ali Samsudin, Ahmad Nurulazam Md Zain, Sayedh Mahbooheh Jamali dan Nader Ale Ibrahim (2017), dan kajian Mohd Zuri Ghani, Nik Rusila Nik Yaacob, Azman Che Ahmad, Rahimi Che Aman dan Zainuddin Mat Isa (2010) yang telah melaporkan bahawa gender tidak mempengaruhi pencapaian dalam pelaksanaan projek STEM dan personaliti kestabilan emosi dalam kalangan murid. Sungguhpun begitu, dapatan kajian ini didapati bertentangan dengan dapatan kajian-kajian lepas yang telah membuktikan bahawa gender mempengaruhi persepi, pencapaian, kebolehan dan menjadi faktor penyumbang kepada keberkesanan proses pembelajaran dalam kalangan murid (Hanita Mohd Yusoff & Norzaini Azman, 2020;Kilia & Saglam, 2010;Chang, Zamri Mohamad & Hamidah Yamat, 2013;Zamri Mahamod & Noor Syazwani Rani, 2013;Haslina Hassan, Ramlah Mailok & Mashitah Hashim, 2019;Tang, Zarinah & Rumaya, 2020;Glowka, 2014;Wehrwein, Lujan & Dicarlo, 2007;Thomas & Allen, 2006;Poh, & Mellissa, 2008;Jackman & Morrain-Webb, 2019;Abdul & Mariyam, 2017;Ayesha, Raneem, Nasser & Nada, 2013). Justeru, gender dibuktikan memberikan persepsi dan tanggapan yang berbeza-beza dan perlu diberikan perhatian dalam proses pembelajaran.…”
Section: Perbincangan Kajianunclassified